The Future of AR-Driven Immersive Classrooms: Pedagogical Impacts for the Next Generation - Sahib, Abdul; Waahib, Achmad Nashrul; Syahputra, M.; Aminah, Aminah; Prastawa, Singgih (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The integration of Augmented Reality (AR) technology in educational environments has the potential to revolutionize classroom dynamics by creating immersive, interactive learning experiences. This research is based on the growing need to explore how AR-driven classrooms can enhance pedagogy and cater to the learning styles of the next generation. AR offers unique opportunities to create more engaging, personalized, and collaborative learning environments, aligning with the educational goals of the 21st century.. Purpose. This research investigates the pedagogical impacts of AR in immersive classrooms, explicitly focusing on student engagement, knowledge retention, and collaborative learning. It aims to evaluate how AR can transform traditional teaching methods and better prepare students for future technological landscapes. Method. The research employs a mixed-methods approach, combining qualitative and quantitative data collection techniques. Surveys and interviews were conducted with educators and students in AR-enabled classrooms, and performance data were analyzed to assess learning outcomes. AR applications across various subjects, including science, history, and the arts, were evaluated to determine their effectiveness in enhancing the learning experience. Results. Findings indicate that AR significantly improves student engagement, increases knowledge retention, and fosters greater student collaboration. The immersive nature of AR motivates students to participate actively in lessons, creating deeper connections with the content. Conclusion. In conclusion, AR-driven immersive classrooms can potentially reshape educational practices, offering new pathways for experiential learning. The integration of AR technology into classrooms holds promise for the future of education by aligning pedagogical approaches with the needs of the digital generation.